PERAN PAJAK CAPITAL GAIN DALAM MENEKAN SPEKULASI BERLEBIHAN DAN MENSTABILKAN HARGA TANAH: TINJAUAN PUSTAKA DAN IMPLIKASINYA TERHADAP KEBIJAKAN FISCAL - Loso Judijanto (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This study examines the role of capital gains tax in curbing excessive speculation and stabilising land prices, as well as its implications for fiscal policy in Indonesia. Excessive speculation in the land market causes high price volatility and inequality in land ownership distribution. Capital gains tax as a fiscal instrument is considered effective in reducing speculation incentives by taxing profits from land sale and purchase transactions, thereby encouraging long-term investment behaviour and more productive land use. Through a literature review and policy analysis, this study shows that the implementation of a progressive capital gains tax supported by a sound tax administration system can contribute to land price stability and increased state revenue, while also supporting social justice and sustainable development.